2015
DOI: 10.1681/asn.2014090886
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming of Branching Morphogenesis in the Kidney

Abstract: The kidney developmental program encodes the intricate branching and organization of approximately 1 million functional units (nephrons). Branching regulation is poorly understood, as is the source of a 10-fold variation in nephron number. Notably, low nephron count increases the risk for developing hypertension and renal failure. To better understand the source of this variation, we analyzed the complete gestational trajectory of mouse kidney development. We constructed a computerized architectural map of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 31 publications
6
55
0
Order By: Relevance
“…Once again, comparison of the ductal network statistics obtained from measurements made during embryonic development with numerical simulations generated from the branching-annihilating random walk paradigm showed remarkably good agreement over a range of developmental time points . In particular, the data indicated that, although branching was seemingly stereotypic early in development, with most tips belonging to similar generations, this changed markedly post E15.5 (Sampogna et al, 2015), with considerable widening of the tip generation numbers, consistent with the predictions of the model. Quantitatively, by adjusting the two parameters of the theory -the ratio of the branching and elongation rates, and the contact radius of tip annihilation, good quantitative agreement was found for the variation of termination probability with branch index, as well as the distribution of branch number, subtree size and subtree persistence across a range of developmental time points.…”
Section: Duc Tal Morphog Ene S Is Of the Mous E K Idne Y And Pan Crsupporting
confidence: 67%
See 2 more Smart Citations
“…Once again, comparison of the ductal network statistics obtained from measurements made during embryonic development with numerical simulations generated from the branching-annihilating random walk paradigm showed remarkably good agreement over a range of developmental time points . In particular, the data indicated that, although branching was seemingly stereotypic early in development, with most tips belonging to similar generations, this changed markedly post E15.5 (Sampogna et al, 2015), with considerable widening of the tip generation numbers, consistent with the predictions of the model. Quantitatively, by adjusting the two parameters of the theory -the ratio of the branching and elongation rates, and the contact radius of tip annihilation, good quantitative agreement was found for the variation of termination probability with branch index, as well as the distribution of branch number, subtree size and subtree persistence across a range of developmental time points.…”
Section: Duc Tal Morphog Ene S Is Of the Mous E K Idne Y And Pan Crsupporting
confidence: 67%
“…Interestingly, tip arrest in these explants was shown to be dependent on Bmp7, a member of the TGFβ super‐family (Davies et al., ), which hints that the core findings from mammary gland could be translatable in other organs. Therefore, based on published data on the detailed structure of three‐dimensional kidney morphogenesis in vivo (Sampogna, Schneider, & Al‐Awqati, ), the question of whether there is a statistical basis to the branching network topology was addressed (Hannezo et al., ). Notably, in the three‐dimensional system, as well as the measured ratio of ductal elongation to branching rates, a second parameter had to be considered – the contact distance within which active tips become terminated against maturing ducts.…”
Section: Ductal Morphogenesis Of the Mouse Kidney And Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…The branching occur in sequence: first, side branching creates the primary stalks; then, there is a change of mode to tip splitting. The kidney developmental program encodes the intricate branching and organization of approximately 1 million functional units (nephrons) [9]. These phenomena have been hypothesized to be under genetic controls [7,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Serum deprivation, which is used to mimic malnutrition, was found to down-regulate the spontaneous calcium activity and to retard nephron formation. In the current study, we have characterized this spontaneous calcium activity using kidneys derived from 14-d-old rat embryos (9). After having identified the endoplasmic reticulum (ER) as the major source of spontaneous calcium signals in the embryonic rat kidney, we examined how those signals contribute to regulation of branching morphogenesis during embryonic kidney development.…”
mentioning
confidence: 99%